Three New Additions to the Flora of United Andhra Pradesh - Rasingam, L.; Swamy, J.; Sankara Rao, M.; Nagaraju, S. (Indian Forester, 2016)
Three species viz., Trichosanthes bracteata (Lam.) Voigt (Cucurbitaceae), Leucas lanata Wall. ex Benth. var. candida Haines (Lamiaceae), Cyperus pulchellus R.Br. (Cyperaceae) are reported here as additions to the flora of united Andhra Pradesh. Detailed descriptions and line drawings are provided for easy identification.